Developing indicators to measure post‐disaster community recovery in the United States. Issue 1 (14th March 2016) - Horney, Jennifer; Dwyer, Caroline; Aminto, Meghan; Berke, Philip; Smith, Gavin
Abstract : Disaster recovery is a key capability of federal, state, and local government. To support this capability effectively practitioners need useful and validated metrics to document how well a community is recovering from a particular disaster. This study developed and categorised recovery indicators according to the Federal Emergency Management Agency (FEMA)'s Recovery Support Functions and Recovery Mission Area Core Capabilities through a literature review, an evaluation of the pre‐disaster recovery plans for 87 coastal jurisdictions, and a case study of two communities (New Hanover County, North Carolina, and the City of Hoboken, New Jersey). Metrics identified in the literature were validated through the recovery plan review and the case study. The research team also identified sources for both baseline and current status data. Based on these findings, a user‐friendly checklist for practitioners was established, which will be piloted with practice partners during a future disaster recovery initiative.